Antialiayzing scenes of the crooked second order given by general equation - Романюк, О. Н.; Курінний, М. С. (Problems of Informatization and Control, 2007)
The new approach is Offered to antialiayzing crooked second order provided that they are given by general equation. Method is characterized by simplicity to hardware realization